Reduced Regional Cerebral Blood Flow Measured by 99mTc-Hexamethyl Propylene Amine Oxime Single-Photon Emission Computed Tomography in Microgravity Simulated by 5-Day Dry Immersion - Guillon, Laurent; Kermorgant, Marc; Charvolin, Thomas; Bonneville, Fabrice; Bareille, Marie-Pierre; Cassol, Emmanuelle; Beck, Arnaud; Beaurain, Marie; Péran, Patrice; Lotterie, Jean-Albert; Traon, Anne Pavy-Le; Payoux, Pierre (Frontiers in Physiology, 2021)
Neuro-ophthalmological changes defined as spaceflight-associated neuro-ocular syndrome have been reported after long duration space flights. The pathophysiology of this syndrome remains unclear, with the possible involvement of elevated intracranial pressure. Changes in cerebral blood flow have been reported in flight. However, the effects of microgravity on regional cerebral blood flow (rCBF) are not known. We therefore investigated changes in rCBF in a 5-day dry immersion (DI) model. Moreover, we tested thigh cuffs as a countermeasure to prevent potential microgravity-induced modifications in rCBF. 18 healthy male participants underwent 5-day DI with or without a thigh cuffs countermeasure. They were randomly allocated to a control (n = 9) or cuffs (n = 9) group. rCBF was measured 4 days before DI and at the end of the fifth day of DI (DI5), using single-photon emission computed tomography (SPECT) with radiopharmaceutical 99mTc-hexamethyl propylene amine oxime. SPECT images were processed using statistical parametric mapping (SPM12) software. At DI5, we observed a significant decrease in rCBF in 32 cortical and subcortical regions, with greater hypoperfusion in basal ganglia (right putamen peak level: z = 4.71, puncorr < 0.001), bilateral occipital regions (left superior occipital peak level: z = 4.51, puncorr < 0.001), bilateral insula (right insula peak level: 4.10, puncorr < 0.001), and bilateral inferior temporal (right inferior temporal peak level: 4.07, puncorr < 0.001). No significant difference was found between the control and cuffs groups on change in rCBF after 5 days of DI. After a 5-day DI, we found a decrease in rCBF in cortical and subcortical regions. However, thigh cuffs countermeasure failed to prevent hypoperfusion. To date, this is the first study measuring rCBF in DI. Further investigations are needed in order to better understand the underlying mechanisms in CBF changes after exposure to microgravity.